The course of cancer-related insomnia: don't expect it to disappear after cancer treatment - Schieber, Katharina; Niecke, Alexander; Geiser, Franziska; Erim, Yesim; Bergelt, Corinna; Büttner-Teleaga, Antje; Maatouk, Imad; Stein, Barbara; Teufel, Martin; Wickert, Martin; Wuensch, Alexander; Weis, Joachim (Sleep medicine, 2019)
Objective - The study aimed to examine the 12-month course of cancer-related insomnia (CRI) and to identify possible predictors for the prevalence and persistence of CRI. - Methods - This longitudinal multicenter study included N = 405 patients with cancer (56% females, mean age: 58.6 years). CRI was measured by the Insomnia Severity Index (ISI). Socio-demographic and clinical data, as well as psychological parameters (Distress Thermometer, PHQ-9, GAD-7, and EORTC-Fatigue), were assessed at baseline (T1) and 12 months later (T2). - Results - In our sample, a high prevalence of relevant insomnia symptoms (49.4%, ISI > 7) was found, while a clinical insomnia diagnosis was verified in 12.8% (ISI > 14). When insomnia was present at T1, this problem was persistent after one year in 64%. At T2, however, significantly more women suffered from insomnia symptoms (53.3% women vs. 39.3% men; p = 0.003). Insomnia was associated with many clinical and psychological parameters, especially with fatigue (r = 0.5). Multiple regression analysis revealed that, in women, only insomnia at T1 was a significant predictor for insomnia at T2 (R2 = 0.40; F(5) = 12.5; p < 0.001), whereas in men insomnia, depressive symptoms and the use of psychotropic drugs at T1 predicted the extent of insomnia at T2 (R2 = 0.28; F(7) = 9.5; p < 0.001). In all participants, levels of distress, depression, and anxiety decreased from T1 to T2 (p's < 0.016). - Conclusion - Insomnia is a common disorder in cancer patients. Although medical and psychological parameters improved during the 12-month course of cancer treatment, our results show that insomnia is highly persistent, especially in women. This indicates that adequate support for those affected is needed. Clinical Trial Registration Number: DRKS00004860.
Gesehen am 06.02.2020